PHYSICAL ACTIVITY OF CHILDREN IN PRE-SCHOOL AGE IN THE OPINION OF PARENTS AND TEACHERS FROM KINDERGARTENS IN UKRAINE - Nazaruk, Stanislawa; Konowaluk-Nikitin, Helena; Poruchynskyi, Andrii; Dmytrotsa, Olena; Poruchynska, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Bearing in mind the proper development of a young person, attention should be paid to shaping certain habits related to physical activity during childhood. The child's physical activity influences various parameters of his health, both today and in the future. In connection with the implementation of joint research between partner universities: Lesya Ukrainka Eastern European National University and Pope John Paul II State School of Higher Education in Biala Podlaska, Poland there was examined the level of physical activity of children aged 5-6 within one day including factors such as: age, sex, participation in sections in kindergarten and their leisure time. 250 children from kindergartens in Lutsk took part in the research. The research results showed that the majority of children show low activity, which may adversely affect their health. Therefore, there is a necessity to organize various kinds of physical activity classes for children, both in the family and in kindergarten.